2014
DOI: 10.1002/j.2168-0159.2014.tb00285.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐36: The Effects of 4K High Resolution Displays on the Sway of the Human Body A Comparison of 2D and 3D Images

Abstract: The 4K television was developed which had 4 times the pixels for full hi-vision giving a realistic image. in this study, we examined the effects of both 2D and 3D images on this high resolution 4K television.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In another study, the participants (young, old, and older) watched 2D and 3D images on a 4K TV. The results showed that there were differences in body sway among the different age groups showing different misery symptoms [17].…”
Section: Introductionmentioning
confidence: 94%
“…In another study, the participants (young, old, and older) watched 2D and 3D images on a 4K TV. The results showed that there were differences in body sway among the different age groups showing different misery symptoms [17].…”
Section: Introductionmentioning
confidence: 94%